2015
DOI: 10.1152/ajpregu.00196.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lymphatic vessels adapt to mesenteric venous hypertension by becoming weaker pumps

Abstract: Lymphangions, the segments of lymphatic vessels between two adjacent lymphatic valves, actively pump lymph. Acute changes in transmural pressure and lymph flow have profound effects on lymphatic pump function in vitro. Chronic changes in pressure and flow in vivo have also been reported to lead to significant changes in lymphangion function. Because changes in pressure and flow are both cause and effect of adaptive processes, characterizing adaptation requires a more fundamental analysis of lymphatic muscle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Our observations are in line with these previous studies; however, the studies presented herein importantly assess lymphatic dysfunction in the absence of direct injury or surgical manipulation. Likely the impairments in lymphatic vascular function observed in angiotensin II-infused mice could come directly from angiotensin II actions on the endothelium, as angiotensin II can induce endothelial dysfunction ( Gomolak and Didion, 2014 ; Watanabe et al, 2005 ) or perhaps indirectly from angiotensin II infusion-induced hypertension, which reportedly alters lymphatic vascular function ( Dongaonkar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations are in line with these previous studies; however, the studies presented herein importantly assess lymphatic dysfunction in the absence of direct injury or surgical manipulation. Likely the impairments in lymphatic vascular function observed in angiotensin II-infused mice could come directly from angiotensin II actions on the endothelium, as angiotensin II can induce endothelial dysfunction ( Gomolak and Didion, 2014 ; Watanabe et al, 2005 ) or perhaps indirectly from angiotensin II infusion-induced hypertension, which reportedly alters lymphatic vascular function ( Dongaonkar et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a recent study by Dongaonkar  et al. attested the changes in mesenteric lymphatic muscle mechanical properties and the intracellular Ca 2+ in response to sustained mesenteric venous hypertension [56]. They showed that following 3 days of mesenteric venous hypertension, the adaptive response of postnodal mesenteric lymphatic vessels resulted in weaker pumps with decreased cytosolic Ca 2+ concentration.…”
Section: Propelling the Lymph Down The Road: The Physiology Of The Comentioning
confidence: 99%
“…Portal hypertension may also detrimentally affect mesenteric lymph flow. Experimental venous hypertension for several days was reported to cause a decrease in bovine mesenteric lymphatic vessel contractions, in association with decreased [Ca 2+ ] i (275). A sizeable number of other scenarios that could influence lymph composition and flow from the gut remain to be studied, yet it is clear that lymphatic vessels have a key role in the development of either local or systemic inflammation in response to the conditions in the gut.…”
Section: Gastrointestinal Lymphatics and Inflammationmentioning
confidence: 99%